Redefining Working Conditions in Europe - Patricia Vendramin; Agnès Parent-Thirion (Revue Internationale de Politique de Développement)
By the standards of the International Labour Organization (ILO), working conditions in Europe are relatively enviable. This chapter, however, highlights a number of trends that are both counterproductive for companies and harmful for employees and the community. Over the past twenty years, the conditions and forms of work organisation have been changing in ways that no longer meet the evolution of the working population. In particular, they no longer match the high and ‘expressive’ expectations of ever more qualified employees, the increasing number of women in the labour market, changing lifestyles and an ageing workforce. During this time, the notion of ‘quality of work’ has sometimes been high on the political agenda. It is now being taken into consideration at the European level thanks to the new European Pillar of Social Rights and the concept of sustainable work. This chapter explores academic and political discourses on the quality of work and provides a review of working conditions in Europe and current challenges in this area. It is based on successive waves of the European Working Conditions Survey (EWCS) conducted by the European Foundation for the Improvement of Living and Working Conditions (Eurofound). In conclusion, we ask whether the notion of sustainable work can be incorporated into the ILO’s forward-looking approach and become a decisive factor in the future of the world of work.